MANAJEMEN SUMBER DAYA MANUSIA - Samsuni Samsuni (STAI AL FALAH Banjarbaru, 2017)
Human resource management is the planning of organizing, implementing and controlling the human resources within the organization to achieve the objectives effectively and efficiently. Human resources as one of the resources that exist in the organization play an important role in the success of achieving organizational goals. Success or failure depends on the ability of human resources in carrying out its duties and functions. Keywords: Management, Human Resources